Terpenoid emissions of Mediterranean oaks and their relation to taxonomy - Csiky, O; Seufert, G (ECOLOGICAL APPLICATIONS, 1999)
This paper presents results of a laboratory screening study of biogenic emissions from Mediterranean oak species. The experiment aimed at improving our understanding of oak contributions to overall emissions of volatile organic compounds and to the atmospheric chemistry in the Mediterranean area. We measured type and amount of terpenoid emissions (isoprene, mono- and sesquiterpenes) under standard conditions of light and temperature from 14 different Quercus species of Mediterranean and American origin. Tree saplings were exposed in a controlled environment chamber, and leaf-level trace-gas exchange was analyzed with a minicuvette system and gas chromatography, to study the relation between the emission types and emission spectra found and the taxonomy of Quercus. The holarctic group Lepidobalanus and the North American groups Erythrobalanus and Protobalanus were found to be strong isoprene emitters. The Eurasian oak group Sclerophyllodrys emits monoterpenes; Cerris include mostly non-emitters, but also an isoprene and a monoterpene emitter has been found in this group. Results are discussed with respect to their implications for presently used emission scenarios.
Keywords: atmospheric chemistry; BEMA (Biogenic Emissions in the Mediterranean Area; Biogenic emission; chemo-taxonomy; isoprene; Mediterranean Region; Monoterpenes; oak taxonomy; oaks; Quercus; terpenoid emissions; trace-gas exchange; volatile organic compounds (VOCs)

An overview of the Castelporziano experiments - Seufert, G; Bartzis, J; Bomboi, T; Ciccioli, P; Cieslik, S; Dlugi, R; Foster, P; Hewitt, C N; Kesselmeier, J; Kotzias, D; Lenz, R; Manes, F; et al. (Atmospheric Environment, 1997)
This paper reviews the major outcomes of the measuring campaigns performed at the Castelporziano nature preserve near Rome, Italy, by 14 European laboratories as part of the BEMA (Biogenic Emissions in the Mediterranean Area)-project. Six campaigns of 1–4 weeks duration were carried out in different seasons of the years 1993–1994 at semi-continuously running test plots in the nature reserve, representing common Mediterranean vegetation types. The aim was to characterise, at the different test plots, the atmospheric chemical and meteorological situations, the plant biomass and physiology, the type, amount and controls of emissions from different plants by means of branch enclosures, and the BVOC emission fluxes from different ecosystems, by scaling up enclosure data from individual sources, and by measuring fluxes directly by use of micrometeorological methods. An important focus during the initial phase of the five year BEMA-project was the harmonisation and improvement of the analytical, physiological and micrometeorological methods used, and the development and testing of new methods for measuring BVOC fluxes.
Keywords: air chemistry; Biogenic emission; ecophysiology; Mediterranean area; micrometeorology; Vegetation